Pengembangan Sistem berbasis Android Sebagai Pengganti Buku Penghubung untuk Memantau Kecerdasan Anak pada RA Al-Baroroh Menggunakan Metode Prototyping - Fatih Kamala Nurika; Agi Putra Kharisma; Marji Marji (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The liaison book as a communication tool between parents and teachers, in the book the teacher provides information on child development to parents, and parents can also provide feedback in the form of child development when at home. However, the lack of resources as a classroom teacher does not allow them to be able to write down the development of a number of children in a class every day, which must be completed before the children return from school. From the results of the notes made on the connecting book, the teacher is required to provide a final semester evaluation in the form of a conclusion that each child is superior in two areas of intelligence. With the problems that arise, research is carried out by developing a system as a substitute for an Android-based link book that can be used as an assistant for writing a connecting book. In this study, several stages were carried out in its development. First, analysis and specification of requirements, planning, implementation, and testing are carried out. At the stage of analysis and specification of requirements produced 35 functional requirements. in the design in this study using use case diagrams, use case scenarios, sequence diagrams, class diagrams, and there is an algorithm design and database design. The development is implemented in Android studio using the Java language. The system testing process begins with unit testing, integration testing, and validation testing which produces a value of 93.02%. And testing the System Usability Scale with a score of 72.09 which can be categorized as good.